Navigating between resistance and unintentional collaboration: The role of left-wing grassroots associations in the tourist city - Santos, P.; Malet Calvo, D.; Nofre, J. (Urban Studies, 2025)
This article explores the ambivalent role of a grassroots cultural and activist association and its forced displacement between two districts as a result of the rapidly advancing frontier of gentrification in the city of Lisbon (Portugal). Strong institutional and private pressures led to the eviction of the association from its former location in the now gentrified Bairro Alto and its relocation to Intendente, a formerly degraded and excluded area currently undergoing a transition to marginal gentrification. By combining documentary research of secondary sources and exploratory ethnography that includes interviews with key informants, this article examines how the association has navigated between resistance against urban neoliberalism and its own (unwanted) contribution to the dynamics of marginal gentrification. It concludes by highlighting the need to deepen analysis of the ambivalent nature of activist associations campaigning for the right to the city, while providing clues for understanding how grassroots organisations resist, survive and/or collaborate with the manifold processes of urban change.